INVESTIGATING ENGLISH TEACHING STRATEGIES TO REDUCE ONLINE TEACHING OBSTACLES IN THE SECONDARY SCHOOL - Nina Rosiana Putri; Fatimah Mulya Sari (Journal of English Language Teaching and Learning, 2021)
The teachers became the key in teaching-learning activities. Teachers had a relation to the students’ success in learning English. So, the English teachers should know the best strategies should be implemented to teach English. It included the strategies to reduce the obstacles that they experienced in online teaching process. This study generally investigated English teaching strategies to reduce online teaching obstacles in teaching English using E-Learning Madrasah Platform at MAN 1 Bandar Lampung. This research was carried out through a case study. The subjects were four English teachers at MAN 1 Bandar Lampung.  The data were obtained from a questionnaire, an interview, and an observation. The data were analyzed through data collection, data reduction, data display, and conclusion. The findings showed that English teachers applied several strategies to reduce online teaching obstacles in teaching English using E-Learning Madrasah Platform. The strategies were applying asynchronous strategy, using an alternative media to support online teaching process, designing lesson plans, material, and online learning activities properly, explaining the materials through video conferences, instructing the students to do the assignments clearly, assessing the students’ works properly, and giving oral and written feedback to the students’ work to make the students were enthusiastic in boosting their learning achievements. In conclusion, all English teachers could reduce the obstacles aligned with each obstacle found.